Pengaruh Pengetahuan Masyarakat dan Minat Penerapan Nilai Islam Terhadap Keputusan Menggunakan Tabungan Perbankan Syariah (Studi Kasus Masyarakat Kota Langsa) - Faisal Umardani Hasibuan; Rahma Wahyuni (Jurnal Ilmiah Ekonomi Islam, 2020)
Abstract This research is done to determine: (1) the influence of people’s knowledge on the decision tgggo use Islamic Banking product, (2) The influence of Islamic values applicatgion on the decision to use Islamic Banking product (The case study of Langsa Town’s Community). The research uses a quantitative approach. The sampling technique is done by purposive sampling. The research data is collected by distributing quantionnaires to 100 respondent. The analysis techniques used are classic assumption test, multiple regression and hypothesis analysis. Based on the data analysis result by using SPSS version 17 system, it concludes that on adjusted R-Square test, 38.5 %shows relationship and contribution of variables on the people’s knowledge and interest of Islamic values application in influencing the decision tu use the saving products and the remaining 61.5 % is explained by other variables of knowledge and interest in the application of Islamic values have an influence on the decision to use saving products. The results F (simultaneous) F count of 32.014 > 3.09 F table so that it can be concluded that Ha is accepted, meaning that there is a simultaneous influence (together) of people’s knowledge variables and interest in applying Islamic values to the decision to use savings products. T test results (partial) variable knowledge of the decision to use savings products obtained t count of 4.408 > 1.660 t table, it means that Ho is rejected and Ha is accepted. Thus the people’s knowledge variable has a partially significant influence on people’s decisions to use Islamic Banking savings products.